2023
DOI: 10.1002/slct.202302451
|View full text |Cite
|
Sign up to set email alerts
|

Organic Ionic Liquid Grafted Nano‐CeO2: A Highly Efficient Photocatalyst for Hydroxylation of Benzene and Reduction of Cr (VI)

Debarati Chakraborty,
Juri Kalita,
Linkon Bharali
et al.

Abstract: An ionic liquid, namely imidazolium sulfonic acid chloride (ISAC) has been electrostatically grafted over cerium oxide nanoparticles to produce a nanocomposite, nano‐CeO2‐IL. The as‐prepared composite was characterized by various analytical techniques such as XRD, FT‐IR, SEM, TEM, XPS, BET, UV‐DRS, PL, and TGA to confirm the grafting of ISAC over CeO2 NPs. The photocatalytic process is regarded as the method of choice for the elimination of air pollutants because of its great efficiency and relatively benign w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Similar PL spectra (sharp peaks) of CeO 2 -NPs have been associated with electronic transitions. 33 However, such sharp peaks coincide with the electronic structure of the stray light from the excitation source. Therefore, it might not be possible to associate such sharp peaks with electronic transitions from the energy levels of ceria.…”
Section: Resultsmentioning
confidence: 98%
“…Similar PL spectra (sharp peaks) of CeO 2 -NPs have been associated with electronic transitions. 33 However, such sharp peaks coincide with the electronic structure of the stray light from the excitation source. Therefore, it might not be possible to associate such sharp peaks with electronic transitions from the energy levels of ceria.…”
Section: Resultsmentioning
confidence: 98%
“…However, as compared to Cr( vi ), Cr( iii ) is much less harmful owing to its inert 3d 3 structure. 18 Thus, it is essential to reduce toxic Cr( vi ) to the least harmful Cr( iii ). Abinaya et al reported an In-doped Mn 2 O 3 nano photocatalyst for the reduction of hexavalent chromium.…”
Section: Introductionmentioning
confidence: 99%